Lack of association between the interferon-α signature and longitudinal changes in disease activity in systemic lupus erythematosus. Issue 9 (4th September 2008) - Landolt-Marticorena, C; Bonventi, G; Lubovich, A; Ferguson, C; Unnithan, T; Su, J; Gladman, D D; Urowitz, M; Fortin, P R; Wither, J
Abstract : Objective: To study the longitudinal expression of interferon (IFN)-inducible genes in systemic lupus erythematosus (SLE) and determine their suitability as disease biomarkers. Methods: RNA was isolated from the peripheral blood of 94 patients with SLE and 11 controls and reverse transcribed into cDNA. The expression levels of five IFN-responsive genes ( LY6E, OAS1, IFIT1, ISG15 and MX1 ) were determined by quantitative PCR, normalised to GAPDH and summed to generate a global IFN score. Patients were followed longitudinally for a period of 3–12 months, and the association between disease activity, as measured by the SLE disease activity index (SLEDAI-2K), and other clinical and laboratory variables was examined. Results: The expression of all five IFN-responsive genes was significantly higher in patients with SLE than in controls. The expression of LY6E, OAS1, IFIT1 and the global IFN score was associated with high disease activity. The global IFN score was also associated with active renal disease, a decreased C3, and the presence of anti-dsDNA or anti-RNA binding protein antibodies at a single point in time. However, there was a poor correlation between changes in this score and changes in disease activity, C3 or anti-dsDNA antibody levels in patients followed longitudinally. In most patients the levels of IFN-induced gene expression remained relatively stable over 3–12 months despite marked changes in disease activity. Nevertheless, in patients with low/moderate disease activity, those with high IFN scores had a more recent history of sustained high disease activity. Conclusion: The findings indicate that IFN-induced gene expression has limited clinical utility as a biomarker of acute changes in disease activity.